Geospatial Analysis of Malaria Prevalence among Children Under Five Years in Jigawa State, North West, Nigeria (African Journal of Biomedical Research, 2024)
Malaria is a contagious disease whose spread is influenced by a number of environmental and anthropogenic factors. It is still regarded as a serious public health concern especially in Africa south of the Sahara. The goal of this study was to use environmental and anthropogenic parameters to create malaria risk map in Jigawa state using GIS (Geographic Information System). Eleven parameters: temperature, rainfall, elevation, slope, distance to rivers, distance to stagnant water bodies, distance to wet lands, distance to roads, population density, LULC (land use/land cover) and distance to healthcare facilities were considered to produced malaria risk map for the area. Multi-Criteria Evaluation (MCE) method was used to map the malaria risk by reclassifying all the factors and assigning weights to each one based on how well-suited they were for the risk of malaria. The final malaria risk map for the area was created using the weighted overlay procedures in the ArcGis spatial analyst tool using assigned values of various risk factors. The malaria risk levels result reveals that 46.07%, 33.71%, 9.94% and 10.28% of the study area fall under low, moderate, high and very high malaria risk levels. This result shows that one-fifth of the study area was subjected to high and very high risk levels of malaria. It is suggested that effective identification and mapping of malaria-risk levels can be made using geospatial tools, to contribute for the prevention and control of this disease.